AB0145 Sodium Chloride Aggravates Arthritis by TH17 Polarization. (10th June 2014) - Jung, S.M.; Kang, J.Y.; Min, H.K.; Koh, J.H.; Suh, Y.S.; Lee, J.H.; Lee, J.; Lee, J.Y.; Kim, J.-M.; Kwok, S.-K.; Park, K.-S.; Park, S.-H.; et al.
Abstract : Background: Recent studies demonstrated that sodium chloride (NaCl) can be a risk factor for autoimmune disease through the induction of pathogenic IL-17 producing T helper (Th17) cells. Objectives: This study was aimed to evaluate the potential effect of NaCl on Th17 differentiation in patients with rheumatoid arthritis (RA) and on the inflammation in collagen induced arthritis (CIA) model. Methods: Peripheral blood mononuclear cells (PBMC) obtained from RA patients were cultured under high salt condition, and analyzed using flowcytometry to determine Th17 population. For evaluation of in vivo effect, CIA mice were fed with normal diet (control group) or high salt diet ad libitum (high salt group). Clinical assessment was performed daily based on visual scoring of paw swelling. The arthrogenic differentiation of mouse bone marrow derived cells and mouse splenocytes were evaluated with tartrate-resistant acid phosphatase (TRAP) staining and flowcytometry, respectively. Results: NaCl promoted the induction of Th17 cells from PBMC in RA patients. Th17 differentiation was progressively upregulated as NaCl concentration increased upto 60 mM. Correspondingly, high salt diet exacerbated the arthritis of CIA mice. The arthritis score was considerably elevated in high salt group compared with control group. In high salt group, osteoclast differentiation represented by TRAP activity was more prominent. We also observed the increased expression of CD4+ RORrt+ cells in spleen of high salt fed mice. Conclusions: This study suggests that NaCl can aggravate arthritis via Th17 differentiation. High salt condition can contribute to the development and progression of RA. References: Kleinewietfeld, M., et al., Sodium chloride drives autoimmune disease by the induction of pathogenic T17 cells. Nature, 2013. Wu, C., et al., Induction of pathogenic TH17 cells by inducible salt-sensing kinase SGK1. Nature, 2013. 496(7446): p. 513-7. Acknowledgements: This work was supported by a grant from the Korea Healthcare Technology R&D Project, Ministry for Health, Welfare & Family Affairs, Republic of Korea (A092258). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5138